Influence of Ni-YSZ Electrode Thickness on the Behaviour of Commercial Solid Oxide Electrolysis Cells by Mean of Electrochemical Impedance Spectroscopy. (2nd June 2015) - Nechache, Aziz; Cassir, Michel; Ringuede, Armelle
Abstract : Electrochemical Impedance Spectroscopy (EIS) is used here in a two-electrode configuration to acquire a deeper comprehension of high-temperature solid oxide electrolysis cells (SOEC), distinguishing different phenomena related to electrochemical and degradation processes. Such approach is applicable to any kind of electrochemical cell. In the present study, chronopotentiometry and EIS are combined in order to analyze the influence of Ni-YSZ electrode thickness on the behavior of two commercial SOECs.